1998
DOI: 10.1093/tropej/44.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease in Bahrain: coexistence and interaction with glucose-6-phosphate dehydrogenase (G6PD) deficiency

Abstract: The object was to determine the frequency of glucose-6-phosphate dehydrogenase in Bahraini individuals with HbS as compared to those without HbS. Haemolysates of erythrocytes from 310 Bahraini individuals attending Health Centres were obtained, electrophoresed on cellulose acetate at PH 8.2-8.6, and stained for G6PD. HbS was present in 125 individuals (study group) and in 185 only HbA was present (control group). G6PD deficiency (very low to undetectable) was identified in 59 samples (47 per cent) of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…More than 300 different mutations have been reported in the G6PD gene8; to date, the Human Gene Mutation Database (www.hgmd.cf.ac.uk/) has reported 202 mutations, with 68 pathogenic mutations that belong to Class I (WHO). The Mediterranean mutation (p.S188F) is the most prevalent among Arabs, with 90% frequency in Bahraini patients91011, 87.8% in Northern Iraqi males, 74.2% in Kuwait, and 53.6% in Jordan1213. Limited studies have investigated the incidence of G6PD mutations and their functional role in causing disease among Arab countries.…”
mentioning
confidence: 99%
“…More than 300 different mutations have been reported in the G6PD gene8; to date, the Human Gene Mutation Database (www.hgmd.cf.ac.uk/) has reported 202 mutations, with 68 pathogenic mutations that belong to Class I (WHO). The Mediterranean mutation (p.S188F) is the most prevalent among Arabs, with 90% frequency in Bahraini patients91011, 87.8% in Northern Iraqi males, 74.2% in Kuwait, and 53.6% in Jordan1213. Limited studies have investigated the incidence of G6PD mutations and their functional role in causing disease among Arab countries.…”
mentioning
confidence: 99%
“…These red cells may be better able to deal with oxidative stress, which can precipitate severe hemolytic disease in G-6-PD defi ciency. However, Mohammad et al [16] in a study on the coexistence and interaction of sickle cell disease with G-6-PD deficiency in Bahrain found a positive correlation between G-6-PD defi ciency and sickle cell disease. hemoglobin E trait (Hb AE), and β-thalassemia trait in comparison to normal controls.…”
Section: Resultsmentioning
confidence: 96%
“…[11,12] Similarly, controversy has prevailed regarding the benefi cial, deleterious or neutral effects of G-6-PD deficiency on the clinical status of sickle cell disease. [9,10,[12][13][14][15][16][17] Although both hemoglobinopathies and G-6-PD deficiency are prevalent in malaria endemic areas in India, to the best of our knowledge, no study has ever reported combined conditions in a single individual from India. The present study highlights 29 tribal cases with compound occurrence of hemoglobinopathies and G-6-PD defi ciency in a randomly conducted study in Sundargarh district of northwestern Orissa.…”
Section: Introductionmentioning
confidence: 99%
“…HbS was also reported to occur with other abnormal haemoglobins ( e.g . HbS/D) in the population of Bahrain36, and a high percentage of the SCD patients (47%) had associated G-6-PD deficiency37.…”
Section: Frequency and Distribution Of Sickle Cell Gene Among Arabsmentioning
confidence: 95%